Capillary alginate gel (Capgel™) for the treatment of full-thickness dermal wounds in a hypoxic mouse model. Issue 18 (12th December 2019) - Bosak, Alexander; Kwan, Michael W. C.; Willenberg, Alicia; Perle, Krista M. D. La; Weinstein, David; Hines, Robert B.; Schultz, Gregory S.; Ross, Edward A.; Willenberg, Bradley J.
Abstract: In this study, capillary alginate gel (Capgel ™ ), a collagen and alginate based self-assembling biomaterial, was used as a cellular scaffold for the treatment of ischemic, full-thickness dermal wounds in mice. Capgel ™ was synthesized using copper sulfate to form the initial sol before rinsing and stabilizing the patent capillary structures with carbodiimide chemistry. This crosslinked hydrogel was then injected into ischemic, full-thickness dermal wounds and analyzed via histology after 7 and 10 days to assess wound contracture, granulation bed tissue and vascular structures. Capgel ™ showed good resorbability and was well-invested with infiltrating host cells and vascular structures during and after resorption. GRAPHICAL ABSTRACT: